2022
DOI: 10.3390/agriculture12010065
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Mechanical Properties of Friction, Collision and Compression of Tiger Nut Tubers

Abstract: The mechanical properties of agricultural materials can provide the basis for the design and optimisation of agricultural machinery. There are currently very few studies on the mechanical properties of tiger nut tubers, which is not conducive to the design and development of machinery for their harvesting and processing. To obtain the mechanical parameters of tiger nut tubers, this study investigated the effects of variety (Zhong Yousha 1 and Zhong Yousha 2), moisture content (8%, 16%, 24%, 32% and 40%), conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The same phenomenon could also be observed where the values of θ increased with moisture contents. The same phenomenon was also reported by other researchers (Dauda et al, 2019;Inekwe, 2019;Jan et al, 2019;Larsson, 2019;Mohite et al, 2019;Etim et al, 2021;Kopeć-Jarosz & Wójcik, 2021;Wang et al, 2022;Zhang et al, 2022). As can be observed, all the linear regression lines of the grains showed positive increments but differed in steepness, indicating that θ of the tested grains increased with moisture content.…”
Section: Wall Friction Angle (θ)supporting
confidence: 88%
See 1 more Smart Citation
“…The same phenomenon could also be observed where the values of θ increased with moisture contents. The same phenomenon was also reported by other researchers (Dauda et al, 2019;Inekwe, 2019;Jan et al, 2019;Larsson, 2019;Mohite et al, 2019;Etim et al, 2021;Kopeć-Jarosz & Wójcik, 2021;Wang et al, 2022;Zhang et al, 2022). As can be observed, all the linear regression lines of the grains showed positive increments but differed in steepness, indicating that θ of the tested grains increased with moisture content.…”
Section: Wall Friction Angle (θ)supporting
confidence: 88%
“…The opposite condition occurred in rough rice, as there was a husk layer on the grain. The sliding friction coefficient of tiger nut on steel, aluminum, plexiglass, and polyurethane was reported to have a linear increase in moisture content (Zhang et al, 2022). The same phenomenon was reported for mucuna beans on plywood, aluminum, glass, galvanized steel, and rough wood (Etim et al, 2021).…”
Section: Wall Friction Angle (θ)mentioning
confidence: 65%
“…The contact parameters between tiger-nut tubers and steel plates and those between tiger-nut tubers were obtained by calibration [30,31]. Other parameters were determined by referring to published literature [32][33][34]. On the basis of research by the research group, the contact parameters and mechanical of the selected materials are shown in Tables 4 and 5.…”
Section: Setting the Simulation Parametersmentioning
confidence: 99%
“…These studies can be conducted using the experimental methods of other plant seeds for reference. Many scholars studied the compression characteristics of hazelnut (Cristiana et al, 2015), sorghum grain (Feng et al, 2022), naked oat seed (Zhang et al, 2019;Qiu et al, 2021), almond (Shi et al, 2021), millet (Yang et al, 2015;Sun et al, 2017), and other seeds. The results showed that moisture content, compression direction, and variety affect the destructive force, deformation, and destructive energy of grains.…”
Section: Introductionmentioning
confidence: 99%